Experimental assessment and validation of energy-maximising moment-based optimal control for a prototype wave energy converter - Faedo, Nicolás Ezequiel (2023)
In recent years, a framework for control of wave energy converters (WECs), termed moment-based control, has been developed within the wave energy conversion literature, exhibiting a remarkable performance in terms of energy absorption, while retaining real-time computational capabilities. Nonetheless, to date, practical results regarding moment-based control for WEC systems have been exclusively provided in numerical simulation, i.e. there is currently a lack of ‘real-world’ assessment of this promising control framework. Motivated by this, we present, in this paper, an experimental assessment and validation of moment-based WEC control for a prototype Wavestar wave energy converter, at the tank-testing facilities of Aalborg University, Denmark. In particular, we address the control design and synthesis procedure in an integrated fashion, covering experimental (physically consistent) system identification, unknown-input estimation and forecasting of wave excitation force, and subsequent control law implementation. We demonstrate that the moment-based controller is able to effectively maximise energy absorption from the wave resource in real-time, with a significant and consistent improvement with respect to the defined benchmark case. The results presented and discussed in this paper demonstrate the feasibility of moment-based WEC control, filling the gap between the attractive theoretical aspects associated with such a strategy, and the practical WEC energy conversion application.